Teachers' Multiple Representations on Teaching Fractions at Elementary School: A Commognitive Framework - Ria Norfika Yuliandari; Cholis Sa'dijah; Susiswo Susiswo; Purnomo Purnomo (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research explores how teachers utilize verbal, symbolic, pictorial, and real-life representations using a commognitive framework to support student learning. This research uses a qualitative approach with an exploratory descriptive design. The selection of research subjects was carried out through purposive sampling which was modified to achieve the research objectives. The research focuses on elementary school teachers who have education diplomas and more than 15 years of teaching experience. In this research, our data is in the form of learning video recording data. The collected data was analyzed using the cognition framework and the Lesh Model of multiple representations. The results of this research show two representations that teachers always apply to each commognitive component, namely symbolic representation and real-life representation. Symbolic representations are often used by teachers to solve mathematical problems, especially word problems. Likewise, real life representations are often used because they apply events or occurrences in everyday life. The use of diverse representations has the potential to increase students' understanding and ability to apply fraction concepts in real life.